The Removal of Uranium onto Nanoscale Zero-Valent Iron Particles in Anoxic Batch Systems. (25th May 2014) - Crane, Richard A.; Scott, Thomas B.
Abstract : The removal of uranium (U) onto nanoscale zero-valent iron particles has been studied for uranium-bearing mine water and synthetic uranyl solutions in the presence and absence of dissolved oxygen. The work has been conducted in order to investigate the differential nanoparticle corrosion behaviour and associated mechanisms of U removal behaviour in conditions representative of near-surface and deep groundwater systems. Batch systems were analysed over a 28-day reaction period during which the liquid and nanoparticulate solids were periodically analysed to determine chemical evolution of the solutions and particulates. Analysis of aqueous samples using inductively coupled plasma mass spectrometry recorded near-total U removal after 1 hour of reaction in all systems studied. However, in the latter stages of the reaction (after 48 hours), significant rerelease of uranium was recorded for the mine water batch system with dissolved O2 present. In contrast, less than 2% uranium rerelease was recorded for the anoxic batch system. Concurrent analysis of extracted nanoparticle solids using X-ray diffraction recorded significantly slower corrosion of the nanoparticles in the anoxic batch system, with residual metallic iron maintained until after 28 days of reaction compared to only 7 days of reaction in systems with dissolved O2 present. Results provide clear evidence that the corrosion lifespan and associated U 6+ removal efficacy of nanoscale zero-valent iron replace enhanced in the absence of dissolved oxygen.